Myocardial longitudinal strain, fitness, and heart failure risk factors in young adults. Issue 3 (20th February 2020) - Arenas, Ivan A.; Podesta, Carlos A.; Issa, Omar; Lin, Jeffrey; Brenes, Juan C.
Abstract: Aims: To investigate the relationship between fitness, heart failure (HF) risk factors (age, blood pressure, and obesity), and global/regional myocardial longitudinal strain in young adults undergoing stress testing. Methods: Individuals 25–55 years old without any significant medical history, not taking medications, and with a normal maximal stress echocardiogram were eligible. Global and regional longitudinal strain (LS) was evaluated by 2D speckle tracking echocardiography. Results: One hundred and seventy patients were included, of which 60% were males. The mean age was 43 years old, 49% had optimal blood pressure, and 30% were obese. On average, patients achieved 10.5 (3) METS, and the global LS was −19.9 (3.1) %. Reduced fitness was associated with decreased global longitudinal strain (GLS). Those in the top GLS quartile walked on average 1 minute and 21 seconds longer compared with the lowest quartile ( P  < .001). The effect of fitness on LS was preferential to the mid and apex, such that there was an apex‐to‐base gradient. Obesity was also independently associated with reduced GLS. However, the reduction in LS in obese individuals was more prominent at the base and mid‐walls with relative sparing of the apex. Similar to fitness, aging was also associated with an increase in the apex‐to‐base gradient of LS. Furthermore, diastolic filling parameters correlated distinctively with regional LS. Conclusions: In young adults without cardiovascular disease, low fitness and obesity are independently associated with reduced left ventricular longitudinal strain. There is a differential effect of HF risk factors on regional longitudinal function.